FRI0291 Characterisation of monocyte populations in peripheral blood of sle patients. (12th June 2018) - Anderson, S.M.; Shah, D.; Webb, D.; Adusumalli, P.; Visvanathan, S.; Fine, J.; Nabozny, G.; Ramanujam, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune diseases characterised by dysregulation of immune cell function with numerous clinical manifestations. Along with B and T cells, myeloid cells play an important role in disease pathogenesis. Circulating monocytes are recruited to sites of inflammation where they play an active role in mediating tissue inflammation and injury. Objectives: To understand the changes in circulating monocyte phenotypes in SLE patients. Methods: Peripheral blood was collected from 25 female SLE patients who were autoantibody positive (dsDNA/Ro/La/SM), with SLEDAIs between 2 and 6 (all patients on hydroxychloroquine, 6 patients on steroids, and 3 on MMF); TR BIO Inc, Hawthorne, NY). Gender matched healthy controls (27 HC) were obtained from BI volunteers. Using multicolor flow cytometry, the percent changes in the expression of HLA-DR/DP/DQ, CD163, CD40, CCR1, CX3CR1 and CD11b on CD14 +, CD14 + CD16 +, and CD16 + monocytes were evaluated. In a smaller subset of these patients (8 SLE and 15 HC), circulating endothelial cell (CECs) phenotyping was performed by evaluating: CD45, CD133/1, CD106, CD105, CD31, CD46, CD34, and CX3CL1. Human 38-plex cytokine/chemokine multiplexes (Luminex, Millipore) were used to evaluate serum analytes. To understand the regulation of cytokines and chemokines from the monocyte population, HC monocytes were sorted to 95% purity, stimulated with disease-relevant TLR ligands, and profiled for their analytes. Statistical analyses were performed using GraphPad Prism, version 7, GraphPad Software Inc. and determined by the Mann-Whitney t-test. Results: SLE patients had a significant increase in MFI for CD14 + CD11b + and CD16 + CD11b + and percentages as well as MFI for CD14 + CD163 +, CD16 + CD163 +, and CD14 + CD16 + CD163 + as compared to controls, . An increase in the percentage of CX3CR1 + CD14 + and CD14 + CD16 + monocytes were observed, see table 1. Concurrently, an increase in CX3CL1 percentage was observed in immature circulating endothelial cells (iCECs) (p<0.0366) as compared to HC. Increases in monocyte/macrophage-associated cytokines and chemokine in the serum (pg/mL) of SLE patients compared to HC, respectively, included: sCX3CL1 (478.6±46.19; 235.4±140.8) and MCP-1 (2657±466.2; 648.5±69.6) (p<0.00001), MIP1ß (141.0±10.71; 79.31±10.69) (p<0.0003), and TNFα (59.07±6.64; 29.31±3.15) (p<0.0041. Additionally, the disease severity and endothelial dysfunction associated biomarker VEGF increased in SLE patients (445.6.3±48.1 pg/mL) compared to HC (231.8±47.03 pg/mL) (p<0.0069). Lastly, HC monocyte subsets were stimulated with TLR7 and 8 ligands and supernatants evaluated for the analytes described above, see table 2. Conclusions: Cell surface markers of activation and adhesion increased in SLE monocyte subsets compared to HC. In parallel, increased inflammatory cytokines and chemokines that attract monocytes to tissues were increased in the serum of these patients. Linking a possible source of this increase in serum analytes, HC monocyte subsets were stimulated with disease-relevant ligands and evaluated in culture. Along with increased monocyte expression of CX3CR1, preliminary data demonstrates an increase in CX3CL1 expression on endothelial progenitor cells (EPCs) and immature and mature circulating endothelial cells (iCECs and mCEC respectively) in active disease. Disclosure of Interest: None declared